Study on the formation of three-dimensionally ordered SiO2 photonic crystals on polyester fabrics by vertical deposition self-assembly. Issue 18 (November 2016) - Zhou, Lan; Wu, Yujiang; Chai, Liqin; Liu, Guojin; Fan, Qinguo; Shao, Jianzhong
In order to form a well-ordered structure of SiO2 photonic crystals on polyester fabrics with fewer defects, a series of influential factors such as particle size and monodispersity of colloidal microspheres, evaporation temperature, relative humidity, mass fraction of colloidal microspheres and solvent in vertical deposition assembly were deeply studied, and the complexities of the self-assembly process of colloidal microspheres on polyester fabric substrates were revealed. In different self-assembly conditions, the quality of SiO2 photonic crystals on polyester fabric substrate was investigated by field emission scanning electron microscopy for the morphology of the crystal structures and by spectrometer measurements for their stop band intensities. Under the conditions of suitable sizes and monodispersity (PDI ≤ 0.08) of colloidal microspheres, the high-quality SiO2 photonic crystals with face centered cubic (fcc) array on polyester fabrics were produced at a low evaporation rate by adopting relative humidity of about 60% with a medium mass fraction of 1.0–1.5% SiO2 microspheres at 25℃ with ethanol as the solvent.